Quality systems and standards for a competitive edge - Guasch, J. Luis (Directions in development (Washington, D.C.). Trade., 2007)
Quality systems and standards have a significant impact on market access, export growth, productivity, industrial upgrading, diffusion of innovation, and other central ingredients for reducing poverty and enhancing country competitiveness. This book provides a comprehensive evaluation and blueprint for implementing quality systems for private sector development and trade and competition initiatives. By thoroughly analyzing the diversity of institutions, linkages, and arrangements involved in quality systems and by identifying success factors in country quality strategies, this book provides a.